Future of Triple Helix in Nigeria: Emerging trends and opportunities in University-Industry-Government collaboration - Nwaichi, Peter Ikechukwu; Agoro, Olayiwola; Thankgod Itua, Egbe; Agi, Augustine Aja; Abdulmalik, Halilu; Nwaichi, Eucharia Oluchi (Springer Nature, 2025)
This work examines the current state of the Triple Helix model in Nigeria, focusing on collaboration among universities, industry, and government to drive innovation, research commercialization, and socio-economic development. Through a qualitative analysis of literature, reports, case studies, and interviews with key stakeholders, the study identifies challenges and emerging trends in the implementation of the Triple Helix model in Nigeria. Findings reveal that, while there has been progress in adopting the Triple Helix approach, several obstacles remain, including weak institutional frameworks, insufficient funding for research and development, limited university-industry collaboration, and the absence of a cohesive policy framework to foster innovation. However, recent trends indicate a growing government interest in innovation, the establishment of university-based innovation hubs, industry-backed academic research, and the development of science parks to support entrepreneurship. The study suggests that with better coordination among stakeholders and strategic investments in capacity-building, Nigeria could unlock the full potential of the Triple Helix model and spur significant transformation. This work contributes a unique perspective by grounding its analysis in real-world examples from Nigeria and offering actionable recommendations for policymakers, universities, and industry leaders to strengthen the Triple Helix framework. These insights could influence policy decisions on research and innovation, potentially leading to job creation, improved technology transfer, and broader socio-economic benefits in sectors such as agriculture, health, and information technology. The paper also identifies directions for future research, including quantitative studies on the impact of Triple Helix collaborations on economic growth, sector-specific engagement analysis, and comparative studies with other countries to provide a global perspective. The value of this paper lies in its roadmap for advancing Nigeria's knowledge-driven economy through enhanced university-industry-government collaboration.